Search of the correlation berween anxiolytic effect of original derivative of pyrrolo [1,2-A] pyrazine TSPO-LIGAND (GML-1) and its concentrations in the rat blood plasma - M. A. Yarkova; A. A. Litvin; G. B. Kolyvanov; V. P. Zherdev; S. B. Seredenin; V. I. Gegechkori (LLC "Publisher OKI", 2018)
Resume. Comparison of "concentration-effect" relation for a new potential anxiolytic drug GML-1, being TSPO Ligand was carried out. GML-1 was administered in rats once, intragastricaLLy in the dose 1 mg/kg. Tested drug concentrations in the rat bLood plasma and animaLs behavior in the test of "eLevated pLus maze" were evaLuated. A vaLue of GML-1 anxioLytic effect does not correLate to concentration in the rat bLood pLasma.